Lactate dehydrogenase A inhibitors with a 2,8-dioxabicyclo[3.3.1]nonane scaffold: A contribution to molecular therapies for primary hyperoxalurias - Alejo-Armijo, Alfonso; Cuadrado, Cristina; Altarejos, Joaquin; Fernandes, Miguel X.; Salido, Eduardo; Diaz-Gavilan, Monica; Salido, Sofia (Bioorganic chemistry, 2022)
[Display omitted] •New family of A-Type proanthocyanidins analogues were synthesized as LDHA inhibitors.•Some analogues are 10-fold more potent than other phenolic flavone-based LDHA inhibitors.•Two novel analogues show a specific inhibition of the isozyme LDHA (versus LDHB).•Novel dioxabicyclic compounds decrease oxalate production by hyperoxaluric hepatocytes.•Targeting LDHA with dioxabicyclic compounds shows potential for therapy in primary hyperoxalurias. Human lactate dehydrogenase A (hLDHA) is one of the main enzymes involved in the pathway of oxalate synthesis in human liver and seems to contribute to the pathogenesis of disorders with endogenous oxalate overproduction, such as primary hyperoxaluria (PH), a rare life-threatening genetic disease. Recent published results on the knockdown of LDHA gene expression as a safe strategy to ameliorate oxalate build-up in PH patients are encouraging for an approach of hLDHA inhibition by small molecules as a potential pharmacological treatment. Thus, we now report on the synthesis and hLDHA inhibitory activity of a new family of compounds with 2,8-dioxabicyclo[3.3.1]nonane core (23–42), a series of twenty analogues to A-type proanthocyanidin natural products. Nine of them (25–27, 29–34) have shown IC50 values in the range of 8.7–26.7 µM, based on a UV spectrophotometric assay, where the hLDHA inhibition is measured according to the decrease in absorbance of the cofactor β-NADH (340 nm). Compounds 25, 29, and 31 were the most active hLDHA inhibitors. In addition, the inhibitory activities of those nine compounds against the hLDHB isoform were also evaluated, finding that all of them were more selective inhibitors of hLDHA versus hLDHB. Among them, compounds 32 and 34 showed the highest selectivity. Moreover, the most active hLDHA inhibitors (25, 29, 31) were evaluated for their ability to decrease the oxalate production by hyperoxaluric mouse hepatocytes (PH1, PH2 and PH3) in vitro, and the relative oxalate output at 24 h was 16% and 19 % for compounds 25 and 31, respectively, in Hoga1-/- mouse primary hepatocyte cells (a model for PH3). These values improve those of the reference compound used (stiripentol). Compounds 25 and 31 have in common the presence of two hydroxyl groups at rings B and D and an electron-withdrawing group (NO2 or Br) at ring A, pointing to the structural features to be taken into account in future structural optimization.